Ancestralidad Con-ciencia de etnia y género en el Valle del Cauca - Zamudio Tobar, Gladys; Giraldo García, Luz Karime (Universidad Santiago de Cali, 2025)
The work entitled "Ancestrality with the Awareness of Ethnicity and Gender in the Cauca Valley" raises topics that are part of the scenarios, challenges, and demands of science, technology, and innovation, from which it is possible to reflect critically and constructively on the training of Afro-descendant and Indigenous girls and adolescents in research, scientific, technological, and innovation skills and abilities, potentially articulated with their ancestral knowledge within these ethnic groups.